2010
DOI: 10.1038/ejhg.2010.169
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial cardiomyopathies: how to identify candidate pathogenic mutations by mitochondrial DNA sequencing, MITOMASTER and phylogeny

Abstract: Pathogenic mitochondrial DNA (mtDNA) mutations leading to mitochondrial dysfunction can cause cardiomyopathy and heart failure. Owing to a high mutation rate, mtDNA defects may occur at any nucleotide in its 16 569 bp sequence. Complete mtDNA sequencing may detect pathogenic mutations, which can be difficult to interpret because of normal ethnic/geographic-associated haplogroup variation. Our goal is to show how to identify candidate mtDNA mutations by sorting out polymorphisms using readily available online t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 35 publications
2
30
0
2
Order By: Relevance
“…Additionally, the results agreed with the next following research in nucleotide behaviors that may be related to strength of the chemical bonds in spite of different area investigations also some of them called guanine an ancestral nucleotide as the most conserved nucleotide [51][52][53][54].…”
Section: Estimation Of Transition/transversion Matrix By Maximum Compsupporting
confidence: 78%
“…Additionally, the results agreed with the next following research in nucleotide behaviors that may be related to strength of the chemical bonds in spite of different area investigations also some of them called guanine an ancestral nucleotide as the most conserved nucleotide [51][52][53][54].…”
Section: Estimation Of Transition/transversion Matrix By Maximum Compsupporting
confidence: 78%
“…Recent studies checking for pathogenic mutations have identified nonsynonomous mutations in mitochondrial genes encoding mt-ND4 and mt-CyB, cytochrome c oxidase I (mt-CO1), and mt-ATP6 in patients with confirmed and suspected cardiomyopathy (36). Like in T2DN mtFHH , the presence of these mutations in humans may indicate increased susceptibility to undergo cardiac remodeling in a setting of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial cardiomyopathy has been associated with numerous mutations in both mitochondrial and nuclear DNA-encoded genes (14,(35)(36)(37)(38). Our data indicate that genetic lesions affecting Mediator complex subunits should also be considered as a possible cause of primary cardiomyopathies in humans, particularly in pediatric cases given the importance of MED30 to early cardiac function during the period of weaning in mice.…”
Section: Dissection Of Moribund Med30mentioning
confidence: 98%